PENGARUH KOMPENSASI FINANSIAL, KOMPENSASI NONFINANSIAL DAN KEPUASAN KERJA TERHADAP SEMANGAT KERJA KARYAWAN LEMBAGA BIMBINGAN BELAJAR SMART EDUCAFE YOGYAKARTA - Azis Abdullah Maulana Yusuf (JURNAL EKOBIS DEWANTARA, 2019)
This study aims to analyze the effect of financial compensation on morale, the effect of nonfinancial compensation on work morale, the effect of job satisfaction on work morale and the effect of financial compensation, non-financial compensation, work satisfaction together - equally influencing the work spirit of smart educafe yogyakarta tutoring institution employees . The population in this study were all 46 employees of the Yogyakarta smart educafe tutoring institution. The method of data collection uses the questionnaire method, while the data analysis technique uses multiple regression analysis which is supported by the F test and T test as well as the classic assumption test consisting of multicollinearity test, normality test, and heterocedasticity test. The results of the study with a significance level of 5% or 0.05 showed that Financial Compensation did not significantly influence Work Spirit with a significance level of 0.089> α 0.05. Non-financial compensation significantly influences work morale with a significance level of 0.025 <α 0.05. Job satisfaction does not significantly influence work morale with a significance level of 0.059> α 0.05. Simultaneously the variables of Financial Compensation and Job Satisfaction have no significant effect on employee morale while Nonfinan Compensation has a significant effect on employee morale with α 5%.